Comparing Crowdfunding Mechanisms: Introducing the Generalized Moulin-Shenker Mechanism - Andrej Woerner; Sander Onderstal; Arthur Schram (Tinbergen Institute, 2022)
For reward-based crowdfunding, we introduce the strategy-proof Generalized Moulin-Shenker mechanism (GMS) and compare its performance to the prevailing All-Or-Nothing mechanism (AON). Theoretically, GMS outperforms AON in equilibrium profit and funding success. We test these predictions experimentally, distinguishing between a sealed-bid and a dynamic version of GMS. We find that the dynamic GMS outperforms the sealed-bid GMS. It performs better than AON when the producer aims at maximizing funding success. For crowdfunding in practice, this implies that the current standard of financing projects could be improved upon by implementing a crowdfunding mechanism that is similar to the dynamic GMS.
Keywords: 330